Marvin K. Mooney, will you please go now!. - Seuss, Dr. (New York, Random House, 1972)
Suggests in rhyme a number of ways for Marvin K. Mooney to travel as long as he gets going--now!
3 6 8 9 10 11 12 13 15 18 19 21 26 29 30 31 33 36 38
Keywords: Stories in rhyme; Fantasy